Gauging the Motivation Level of Health Personnel of a Tertiary Care Hospital in District Dehradun - Sharma, Neha; Saini, Ravinder; Semwal, Jayanti; Vyas, Shaili; Srivastava, Abhay; Chaturvedi, Manish (Indian Journal of Community Health, 2023)
Background- Healthcare providers serve as the backbone of the healthcare delivery system, and motivating them is crucial for its enhancement, which is often a challenging task. Understanding the motivational factors that keep employees engaged is a pressing concern for leaders and senior personnel. Aims & Objectives: This study aimed to assess the motivation levels of healthcare personnel working in a tertiary healthcare institution in Dehradun, Uttarakhand. It sought to explore the various factors influencing employee motivation in the healthcare sector. Methodology: A cross-sectional study involved 150 healthcare personnel, and data analysis was conducted using Statistical Package for Social Sciences (SPSS) software and Microsoft Excel. Frequency percentages and mean standard deviations were used for categorical and continuous data, respectively. The Chi-Square test and Fischer Exact test were employed to assess relationships between categorical variables. Results: Among the study groups, technicians displayed the highest motivation levels, while doctors exhibited lower motivational indices. Across doctors, nurses, and technicians, "rewards" ranked as the top motivating factor. Health personnel identified monetary support, incentives, promotion, resource improvement, appreciation, feedback, communication, job security, training, teamwork, and effective management as significant motivational factors. Conclusion: Satisfied healthcare workers not only inspire their colleagues but also foster a positive work environment, enhancing the overall functioning of the institution. Employee motivation directly impacts the performance of healthcare organizations. Recognizing non-financial motivators, such as appreciation, teamwork, professional growth, and training, alongside financial incentives, is essential to maintaining a motivated and efficient healthcare workforce.